2022
DOI: 10.1007/s00405-022-07676-1
|View full text |Cite
|
Sign up to set email alerts
|

Internal auditory canal volume in normal and malformed inner ears

Abstract: Purpose A narrow bony internal auditory canal (IAC) may be associated with a hypoplastic cochlear nerve and poorer hearing performances after cochlear implantation. However, definitions for a narrow IAC vary widely and commonly, qualitative grading or two-dimensional measures are used to characterize a narrow IAC. We aimed to refine the definition of a narrow IAC by determining IAC volume in both control patients and patients with inner ear malformations (IEMs). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
5
0
3
Order By: Relevance
“…According to other studies in the literature, the width of the IAC correlates with the occurrence of inner ear malformations and bilateral sensorineural hearing loss. 24 , 25 Another study 16 revealed that the width of the IAC in individuals with inner ear malformations did not show a significant correlation with the number of Spiral Ganglion Neurons (SGNs) or the presence of aplastic/hypoplastic cochlear nerves. Our study considered a narrowed IAC less than 3 mm wide.…”
Section: Discussionmentioning
confidence: 99%
“…According to other studies in the literature, the width of the IAC correlates with the occurrence of inner ear malformations and bilateral sensorineural hearing loss. 24 , 25 Another study 16 revealed that the width of the IAC in individuals with inner ear malformations did not show a significant correlation with the number of Spiral Ganglion Neurons (SGNs) or the presence of aplastic/hypoplastic cochlear nerves. Our study considered a narrowed IAC less than 3 mm wide.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the identification and accurate measurement of the VA is challenging even in subjects with normal anatomy and a correct assessment of VA volume. Consequently, this is even more difficult in patients with IEM [ 28 30 ]. The present study provides evidence that measuring VA width may not accurately distinguish EVA from normal VA. Variations in the VA shape as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Общеизвестно, что при выборе системы КИ должны учитываться анатомия внутреннего уха, аудиологические данные, возраст и индивидуальные анатомо-физиологические особенности мягких тканей головы и костей черепа [7,12,14,20,25,33,41,52].…”
unclassified
“…Как известно [2,6,10,20,24,38,45,50], аномалии улитки являются результатом торможения эмбриогенеза, анормального ее развития во время отдельных этапов внутриутробного периода или генетических дефектов. Считается также, что может происходить инактивация одного или нескольких генов, которые являются ответственными за нормальное развитие внутреннего уха [2,5,13,25,31,36,44].…”
unclassified
See 1 more Smart Citation